Analysis of the performance of myocardial revascularization in patients hospitalized by the Brazilian Unified Health System in the last 10 years (Research, Society and Development, 2023)
The objective of this research is to analyze the comparison, creating a temporal analysis, of hospitalizations, average value per hospitalization and mortality rates, among all Brazilian regions, with regard to coronary artery bypass grafting (CABG). This is an ecological study, with a quantitative approach and analysis of temporal sequences. The Brazilian population that underwent CABG between 2012 and 2022 in hospitals in Brazil, whose procedures were financed by the Unified Health System (SUS), was surveyed. For the temporal analysis of the rate sequences, the following variables were defined: Admissions; Region (North, Northeast, Midwest, South and Southeast); Mortality rate; Mean AIH Value; Amount. According to the DATASUS database, during the period from 2012 to 2022, throughout Brazil, of the 124,947,182 hospitalizations confirmed by the SUS, 228,765 CRMM (0.18%) were identified throughout Brazil. Evidencing a predominance of hospitalization in the South region, with an average value of R$ 13,200.42 in Brazil and an increasing mortality rate.